An Empirical Analysis of The Stochastic Implications of Stock Price Movements in The Nigerian Capital Market - Whisky, Ayakeme E. (Archives of Business Research, 2014)
The study provides further empirical insight on the behavior of stocks in four selected sectors of the Nigerian economy using the Runs and GARCH techniques to analyze monthly stock data for the period January to December, 2011. The results of the Runs Test do not support random movements of stocks in all the sectors, indicating homoscedasticity. The GARCH estimated model also shows volatility clustering in all the sectors except the Agricultural sector, which implies weak form inefficiency of the Nigerian capital market. Keywords: Randomness; stochastic movements; runs; GARCH; homoscedasticity; heteroscedasticity; Nigeria